Management of Quebec Platelet Disorder for Cervical Facet Injections in the Outpatient Setting: A Case Report. Issue 6 (April 2020) - Lee, Debbie; Walega, David R.
Abstract : Quebec platelet disorder (QPD) is a condition that causes delayed-onset bleeding after hemostatic challenges. While there are interventional spine procedure (ISP) guidelines for managing patients on blood thinners or with common bleeding disorders, there are none for approaching patients with unique coagulopathies. We report a patient with QPD and extensive history of postprocedural bleeding complications (PPBCs) who presented with chronic cervical facet pain. After consulting a hematologist and administering antifibrinolytic agent with platelet transfusions, the patient underwent medial branch nerve blocks (MBNBs) followed by radiofrequency ablation (RFA) without experiencing PPBCs. A comprehensive team approach is critical to maximize patient safety when performing an ISP in such a population.